5 times revenge - Eland, Lindsay (Greenwillow Books, an imprint of HarperCollins Publishers, 2016)
"Adam is the prank mastermind. Perk is his best friend and the computer genius. Pearl is the prettiest girl in school, and a violin prodigy. Ray looks like a big dumb jock, but he secretly wants to be an engineer. And Dutch is the often-bullied dork who is in tune with everyone's feelings. The five of them couldn't be more different. But there's one thing they have in common: they are fed up with Hill Parmar, the school bully-and his dad, their school principal who's always turning a blind eye"--Publisher.